개선된 GOP 단위의 스무딩 알고리즘 - 이면재(Myoun-Jae Lee) (디지털콘텐츠학회논문지, 2011)
스무딩은 가변 비트율로 저장된 비디오 데이터를 클라이언트로 전송할 때 일련의 고정 비트율로 전송할 수 있도록 전송 계획을 세우는 것으로 이러한 스무딩 알고리즘에는 CBA, MCBA, MVBA 등이 있다. 그러나, 이 알고리즘들은 프레임 단위로 전송 계획을 세우므로 프레임 버스트 또는 GOP 버스트가 발생할 수 있다. 이를 개선하기 위하여 MVBAG 알고리즘에서는 GOP 단위로 전송률을 계산한다. 그러나, 이 알고리즘에서는 계산된 전송률보다 급격히 프레임의 크기가 작거나 큰 경우에는 QoS를 보장하지 못할 수 있다. 본 논문에서는 MVBAG 알고리즘의 문제점을 개선하는 알고리즘을 제안하고 QoS를 만족시키지 못하는 프레임 개수, 프레임당 평균 전송률 변화량, GOP당 평균 전송률 변화량과 같은 평가 요소를 사용하여 성능을 평가한다. 실험 결과, 제안 알고리즘은 QoS를 만족하는 프레임 개수 비교에서 우수함을 보인다. Smoothing is a transmission plan where variable rate video data is converted to a constant bit rate stream. These smoothing algorithms include CBA, MCBA, MVBA, PCRTT and others. But, these algorithms build a transmission plan per frame unit. So, these algorithms cause frame burst or GOP burst. In order to improve it, MVBAG algorithm build a transmission plan per GOP. But this algorithm may not guarantee QoS when frame's size is abruptly larger or smaller than the computed transmission rate. In this paper, a smoothing algorithm is proposed to enhance MVBAG algorithm's problem. In order to show the proposed algorithm's performance, the proposed algorithm is compared with MVBAG algorithm using various evaluation factors such as number of frames that do not meet the QoS, average transmission rate variability per frame, average transmission rate variability per GOP. Experimental results show that the proposed algorithm outperforms MVBAG algorithm in number of frames that do not meet the QoS. KCI Citation Count: 0